Peran Dan Tanggung Jawab Pihak Rumah Sakit Dalam Pelayanan Kesehatan Terhadap Pasien Pengguna Badan Penyelenggara Jaminan Sosial (Bpjs) Kesehatan - Agusta, Martin; Paramarta, Vip; Purwanda, Eka (Civiliza Publishing, 2024)
This research aims to analyze the role and responsibilities of hospitals in health services for patients using the Health Social Security Administering Agency (BPJS). Optimal health services for BPJS patients are very important, considering the number of beneficiaries continues to increase in Indonesia. A descriptive qualitative approach was used in this research involving in-depth interviews, participant observation, and documentation analysis. Research participants consisted of medical personnel, hospital management, and BPJS patients in several hospitals registered as BPJS Health partners. The research results show that although hospitals have tried to meet BPJS service standards, there are various challenges, including limited resources and gaps in access to health facilities. Apart from that, communication and coordination skills between the hospital and BPJS are also important factors in providing efficient services. This study recommends increasing training for health workers and strengthening the coordination system between hospitals and BPJS to improve the quality of health services for BPJS patients.